Peranan Bakteri Bacillus sp. sebagai Agen Biofertilizer dalam Meningkatkan Kesuburan Tanah dan Produktivitas Tanaman : Kajian Literatur - Yanris Trisyana Mendrofa; Natalia Kristiani Lase (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
The use of fertilizer in plant cultivation is basically carried out to meet the availability of nutrients for plants in order to obtain optimal results. However, excessive use of fertilizer can actually have a negative impact on the ecosystem, such as environmental pollution and decreasing soil quality. The use of biofertilizer as a substitute for biological fertilizer is an alternative that can be used to reduce dependence on chemical fertilizers. Biofertilizer is a biological fertilizer containing various live microorganisms which is used to increase plant productivity by improving the quality of soil fertility. One of the microbes that acts as a biofertilizer is the Bacillus sp. The purpose of this article is to find out how Bacillus sp. functions as a biological fertilizer that can increase soil fertility and increase crop productivity. Bacillus is a genus of bacteria that can be used as a biofertilizer because of its more varied antagonistic mechanisms and ability to produce endospores. The method used in this article is a meta-analysis or literature review method in several journals published online which are integrated with Google Scholar.